2021
DOI: 10.1007/s12288-021-01459-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Von Willebrand Factor Levels Predict Survival in COVID-19 Patients Across the Entire Spectrum of Disease Severity

Abstract: Background: Characterization of reticulo-endothelial activation in COVID-19 may guide treatment. Objectives: To assess reticulo-endothelial activation and its correlation with disease severity and death in patients across the entire spectrum of COVID-19 severity. Methods: Consecutive hospitalized COVID-19 patients were studied, with similar number of patients in each disease severity category. Baseline serum ferritin, sCD163 (macrophage activation markers) and plasma von Willebrand factor (VWF) antigen (endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Plasma levels of ADAMTS13 inhibitors like IL-6, thrombospondin and platelet factor 4 are often elevated in patients with severe COVID-19[36]. Other investigators and groups have drawn similar conclusions[37,[38][39][40][41].Henry et al[42] identified a lower ADAMTS13 activity/VWF:Ag ratio in patients with COVID-19 and acute kidney injury and those who developed infection compared to patient with neither. In a prospective study of 50 patients with COVID-19 requiring hospital admission[34], higher D-dimer, fibrinogen and VWF:Ag levels and lower ADAMTS13 activity were observed compared to patients not requiring hospitalization.…”
mentioning
confidence: 87%
“…Plasma levels of ADAMTS13 inhibitors like IL-6, thrombospondin and platelet factor 4 are often elevated in patients with severe COVID-19[36]. Other investigators and groups have drawn similar conclusions[37,[38][39][40][41].Henry et al[42] identified a lower ADAMTS13 activity/VWF:Ag ratio in patients with COVID-19 and acute kidney injury and those who developed infection compared to patient with neither. In a prospective study of 50 patients with COVID-19 requiring hospital admission[34], higher D-dimer, fibrinogen and VWF:Ag levels and lower ADAMTS13 activity were observed compared to patients not requiring hospitalization.…”
mentioning
confidence: 87%
“…Elevated CD163 expression on alveolar macrophages has been reported in patients with chronic obstructive pulmonary disease (BPCO) and in idiopathic pulmonary fibrosis ( 9 ). Several authors reported an increment of sCD163 plasmatic levels with worsening COVID-19 severity, underlining a preponderant role for monocyte-macrophage activation in the development of immunopathology of COVID-19 patients ( 6 , 15 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The final full-text review included 163 reports, from which 123 studies did not meet the inclusion criteria and were excluded. A total of 40 studies comprising of 3764 patients met the including criteria and were included in this systematic review and meta-analysis [24] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] . Fig.…”
Section: Resultsmentioning
confidence: 99%